The Role of Counselor In Handling Today's Adolescent Problems - Sae, Yunarti; Liufeto, Esti Barnadeta; Nome, Elda Merliance; Lay, Jondris; Banik, Lodia Amelia; Lelo, Kaleb (TRANSFORMASI : JURNAL PENGABDIAN PADA MASYARAKAT, 2025)
The role of counselors is very important in dealing with the problems faced by today’s teenagers, which often involve academic pressure, relationships, family conflicts, and mental health problems such as anxiety and depression. Counselors function as objective listeners, provide emotional support, and help teenagers understand their feelings and overcome the difficulties they face. Through individual and group counseling, counselor guide teenagers to develop effective coping skills, improve interpersonal relationship, and make positive decisions. With an approach based on empathy and communication, counselors play a role in supporting the healthy development of adolescent psychologically, socially and emotionally